Educational Leadership Relationally: A Theory and Methodology for Educational Leadership, Management and Administration - Eacott, Scott (Springer, 2016)
Educational leadership, management and administration has a rich history of epistemological and ontological dialogue and debate. However in recent times, at least since the publication of Colin Evers and Gabriele Lakomski’s trilogy – knowing, exploring and doing educational administration – there has been a distinct dearth. Educational Leadership Relationally explicitly returns matters of epistemology and ontology to the centre of the discussion. Through a sustained and rigorous engagement with contemporary thought and analysis, Scott Eacott articulates and defends a relational approach to scholarship in educational leadership, management and administration. Eacott belongs to a group of scholars in educational administration who could be called meta-sociologist. This group blends sociology, historical revisionism, managerial theories and general philosophy to emphasise the relevance of sociological analysis in the field of educational administration. Proposing a relational turn, Eacott outlines a methodological agenda for constructing an alternative approach to educational leadership, management and administration scholarship that might be persuasive beyond the critical frontier. The relational research programme is arguably the most ambitious agenda in educational leadership, management and administration coming out of Australia since Colin Evers and Gabriele Lakomski’s natural coherentism and Richard Bates’ Critical Theory of Educational Administration. As a research agenda, it engages with: the centrality of administration in constructions of the social world; the legitimation of popular labels such as ‘leadership’; the inexhaustible and inseparable grounding of administrative labour in time and space; and overcomes contemporary tensions of individualism/collectivism and structure/agency to provide a productive – rather than merely critical – space to theorise educational leadership, management and administration.